Towards a Performance Measurement Framework for Community Development Finance Institutions in the UK - Kneiding, C.; Tracey, P. (2012)
Community Development Finance Institutions (CDFIs) are publicly funded organisations that provide small loans to people in financially underserved areas of the UK. Policy makers have repeatedly sought to understand and measure the performance of CDFIs to ensure the efficient use of public funds, but have struggled to identify an appropriate way of doing so. In this article, we empirically derive a framework that measures the performance of CDFIs through an analysis of their stakeholder relationships. Based on qualitative data from 20 English CDFIs, we develop a typology of CDFIs according to three dimensions: organisational structure, type of lending and type of market served. Following on from this, we derive several propositions that consider how these dimensions relate to the financial and social performance of CDFIs, and provide the basis for a performance measurement framework.